The curse of anxiety-pleasure: Terrorism, the media, and advertising in a two-sided market framework - Christoph P. Pfeiffer (Helmut-Schmidt-Universität - Universität der Bundeswehr Hamburg, Fächergruppe Volkswirtschaftslehre, 2012)
In theoretical analyses on terrorism and the media, the structure of the media market has thus far been neglected. The present paper adopts a multi-sided market framework in order to explore the ways in which the markets for terrorism, advertising, and the media influence each other. Although the markets for terrorism and the media do not constitute a two-sided market, they are linked by externalities, the degrees of which can be determined by the media. Further, advertisers play a crucial role in determining the content of a media product because they (i) usually contribute to a large share of a media firm's profit and (ii) value media violence for its juvenescent effect on the age structure of consumers. The model presented herein predicts that the probability of a circulation-advertising-terrorism spiral usually decreases with increasing average age of the population, given that the media firm derives part of its profit from advertisements. The results underline the importance of financially independent news coverage.
Keywords: C72; D62; H52; 330; terrorism; media; advertisements; multi-sided markets; game theory